DINAMIKA PENELITIAN KEPATUHAN WAJIB PAJAK - Sri Ayemi; Yhoga Heru Pratama; Oksidea, Jauzaa Azahroo Oksidea; Fransiskus Vilisianus Sales (FKIP Unswagati, 2024)
This study explores the compliance of taxpayers in Indonesia from 2013 to 2023 by mapping research published in national scientific journals. The research methodology involves a thorough literature review, examining articles with the keyword